Pemaknaan Ulang Ar Riqab dalam Upaya Optimalisasi Fungsi Zakat Bagi Kesejahteraan Umat - Zainuddin Zainuddin (Fakultas Hukum Universitas Islam Indonesia, 2018)
This study raises the issue of, first, reinterpretation of ar-riqab in an effort to optimize the function of zakat for social welfare, and second, contextualization of ar-riqab reinterpretation as a victim of human trafficking crime to optimize the function of zakat for social welfare. This research is doctrinal research with legal and conceptual approaches. The results show that, first, ar-riqab in the conventional terminology as a slave is no longer relevant to the current conditions. Ar-riqab can be understood as a person shackled in structured and massive poverty, making it possible for zakat functioning as a public economic instrument to achieve the success of promoting welfare. Second, one of the meanings of ar-riqab in accordance with the current conditions is victim of human trafficking. This group is vulnerable to economic exploitation, making it difficult to empower themselves because they are in the power of other people. The instrument of zakat as an economic power can play a role for the empowerment of trafficking victims by including them as aznaf ar-riqab. This study recommends that zakat management contextually interprets ar-riqab and is no longer fixated on the meaning of slave, thus enabling optimum functioning of zakat as an instrument to achieve social welfare.